Effect of Financial Literacy and Access to Capital on the Growth of Micro, Small, and Medium Enterprises - Mohammad Rizky Yahya; Ratih Puspitasari; Irmah Halimah Bachtiar; Samalua Waoma; Victor Pattiasina (HM Journals, 2023)
This study aims to determine and analyze effect of financial literacy and access to capital on the growth of Micro, Small, and Medium Enterprises. This study applies a quantitative research design. Population in this research is Micro, Small, and Medium Enterprises in Medan City. Sampling technique used purposive sampling with a sample of 50 respondents from Micro, Small, and Medium Enterprises in Medan City. Testing the hypothesis in this study using multiple linear regression. The results show that financial literacy has a positive and significant effect on the growth of Micro, Small, and Medium Enterprises. Access to capital has a positive and significant effect on the growth of Micro, Small, and Medium Enterprises.